Mild encephalopathy with reversible splenial lesion associated with echovirus 6 infection: a case report and review of the literature - Masiello, Enrico; Gatto, Antonio; Lazzareschi, Ilaria; Rigante, Donato; Mariotti, Paolo; Valentini, Piero (The Turkish Journal of Pediatrics, 2020)
Background. Mild encephalopathy with reversible splenial lesion (MERS), a clinic-radiological syndrome distinguished by reversible encephalopathy onset, has been increasingly recognized in Caucasian children. Case. We describe a MERS case in a previously healthy 4-year-old girl admitted to the hospital with abnormal consciousness level, muscle weakness, dysphagia and dysarthria after a 4-day history of diarrhea and fever. Magnetic resonance imaging (MRI) of the brain showed hyperintensity in the corpus callosum splenium. Electroencephalogram was normal and cerebrospinal fluid (CSF) culture negative. The stool sample was positive for Echovirus 6 and serology test confirmed the infection. The child`s condition gradually improved and the MRI, after 15 days, depicted a normal brain. Only a mild speech impairment was persistent at discharge, which disappeared one month later. We performed a literature review about pediatric MERS cases demonstrating that infectious agents have been rarely isolated in CSF. Conclusion. MERS has an overall good prognosis independently from the treatment approach; this is confirmed by our case - one of the first reported with an Echovirus 6-related encephalopathy.
Keywords: child; echovirus; encephalopathy; mild encephalopathy with reversible splenial lesion (MERS)